Self-reported severe gastrointestinal symptoms are not prevalent in elite female soccer players - Sellors, C. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Gastrointestinal (GI) symptoms during exercise are common in female athletes (Parnell et al, 2020). The prevalence and severity of symptoms varies between athletes, yet common symptoms can negatively impact performance and exercise completion. Pre- during- and post-exercise nutritional intake may be altered in an attempt to reduce GI symptoms and prevent performance detriments (Parnell et al, 2020). However, most research has been conducted in female endurance athletes, with limited data in team sport athletes. Therefore, the aim of this study was to identify the prevalence and severity of GI symptoms, and nutrition habits, in elite female soccer players.